Selective electron beam melting of Ti-48Al-2Nb-2Cr: Microstructure and aluminium loss - Schwerdtfeger, Jan; Körner, Carolin (Intermetallics, 2014)
In the present paper a broad parameter window for processing Ti-48Al-2Cr-2Nb by selective electron beam melting is investigated. Data for the aluminium loss during the process in relation to used beam parameters and process strategies for its minimisation are presented. Al losses as low as 0.5 at% were achieved. Using different beam parameters a wide range of microstructures from lamellar to massively transformed γ could be realized. This finding in principle gives the opportunity to locally adjust the microstructure of net or near-net-shape parts from TiAl during the process. © 2014 Elsevier Ltd. All rights reserved.
Keywords: A. Titanium aluminides; based on TiAl; C. Near-net-shape manufacturing; C. Powder metallurgy; including consolidation; D. Microstructure